2021
DOI: 10.2147/ppa.s342535
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Social Media on the Acceptance of the COVID-19 Vaccine: A Cross-Sectional Study from Saudi Arabia

Abstract: Introduction: Social media platforms are used by many people to seek and share healthrelated information that may influence their decision-making about COVID-19 vaccination. Purpose: The objective of this study is to understand the influence of social media on the attitudes and willingness of the general public of the Aseer region of Saudi Arabia to receive COVID-19 vaccination. Materials and Methods: A cross-sectional self-administrated online survey was conducted in Saudi Arabia Aseer region, where 613 perso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 44 publications
1
20
1
Order By: Relevance
“…Another point to be considered is that there are also plenty of social media accounts that spread misinformation. In a study conducted in Saudi, 74.6% of participants agreed that social media carries wrong information about vaccines [27]. This is further invigorated by various reports on conspiracy theories that have circulated on social media regarding vaccines such as it being linked to nanochip insertion [15, 28].…”
Section: Discussionmentioning
confidence: 99%
“…Another point to be considered is that there are also plenty of social media accounts that spread misinformation. In a study conducted in Saudi, 74.6% of participants agreed that social media carries wrong information about vaccines [27]. This is further invigorated by various reports on conspiracy theories that have circulated on social media regarding vaccines such as it being linked to nanochip insertion [15, 28].…”
Section: Discussionmentioning
confidence: 99%
“…This is supported by studies that reported that more individuals were willing to get COVID-19 vaccination during the lockdown compared to the pre-lockdown period of COVID-19 and, as risk perception increased, so did the intention to accept getting the vaccine [50][51][52]. Social media plays a significant role in COVID-19 vaccination uptake [53,54]. Therefore, it is not surprising that having problematic social media use and cyberchondria are associated with the increased likelihood of participants getting a COVID-19 vaccine.…”
Section: Discussionmentioning
confidence: 78%
“…This indicates that misunderstandings about the disease's origins and vaccination intentions may have a strong impact on COVID-19 vaccine acceptance. Conspiracy theories may be falsely believed as a result of misinformation from various social media outlets, religious beliefs, or peer advice ( 14 , 23 , 24 ). Hence, a structured and well-prepared factual communication by the government and responsible public media is vital to preclude society from misleading conspiracy theories and anti-vaccine information which contributes to the burden of morbidity and mortality from confirmed COVID-19 cases.…”
Section: Discussionmentioning
confidence: 99%